PROFILE OF HOMICIDAL DEATHS: A ONE YEAR STUDY AT P. D. U. MEDICAL COLLEGE, RAJKOT DURING 2018 -19 (Journal of Forensic Medicine & Toxicology, 2020)
Homicide means one human being causes death of another. Not all homicide is murder, as some killings are manslaughter, and some are lawful, such as when justified by an affirmative defence, like insanity or self defence.1 Homicide has been a most heinous crime known to mankind, right from old civilianization to present day, however motives have been changing. It is much more common in countries with law levels of human development, high levels of income inequality and weak rule of law than in more equitable societies, where socio-economic stability seems to be something of an antidote to homicide.2 Women murdered by their past or present male partner make up the vast majority of (female) victims.3 The incidence of homicide has been in-creasing because of several factors; like stresses of life due to monitory, emotional, health issues etc. psychological disturbances during upbringing of child, negative impact of media and movies etc. This increasing trend is also affected by improvisation and sophistication of weapon of violence as well as its easy availability, cosmopolitism of urban areas, propagation of religious hatred feelings and terrorism. The present study throws light on various such aspects related to homicide.
Keywords: investigating; equitable; Homicide; affirmative